POSHAN’s abstract digest on maternal and child nutrition research – Issue 18 - Avula, Rasmi (International Food Policy Research Institute, 2017)
This issue of Abstract Digest features several papers from a UNICEF supported special supplement of Maternal and Child Nutrition on First Foods and papers from a South Asia Infant Feeding Research Network (SAIFRN) supported special supplement on the policy landscape for infant and young child feeding (IYCF) in South Asia. In addition, there are several other interesting articles highlighting the need for equity driven approaches to address malnutrition, factors associated with optimal child growth, and feasibility of engaging women’s collectives in delivering nutrition messages.